2017
DOI: 10.1186/s12955-017-0748-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of health state utility values in head and neck cancer

Abstract: BackgroundHealth state utility values (HSUVs) are essential parameters in model-based economic evaluations. This study systematically identifies HSUVs in head and neck cancer and provides guidance for selecting them from a growing body of health-related quality of life studies.MethodsWe systematically reviewed the published literature by searching PubMed, EMBASE and The Cochrane Library using a pre-defined combination of keywords. The Tufts Cost-Effectiveness Analysis Registry and the School of Health and Rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 76 publications
(208 reference statements)
1
56
0
Order By: Relevance
“…First, the HSUVs applied in our model were derived from previously published studies for head and neck cancer because of the lack of speci c HSUVs for paranasal sinus and nasal cavity cancer. As previously reported, the overall mean HSUV of head and neck cancer survivors after radiotherapy was consistently considered as 0.7 [25,26]. In this study, the survivors after radiotherapy had two different states, namely as "alive with cancer" and "no cancer".…”
Section: Discussionmentioning
confidence: 64%
“…First, the HSUVs applied in our model were derived from previously published studies for head and neck cancer because of the lack of speci c HSUVs for paranasal sinus and nasal cavity cancer. As previously reported, the overall mean HSUV of head and neck cancer survivors after radiotherapy was consistently considered as 0.7 [25,26]. In this study, the survivors after radiotherapy had two different states, namely as "alive with cancer" and "no cancer".…”
Section: Discussionmentioning
confidence: 64%
“…They reported Spearmen coefficients >0.6 between the UWQoL and EQ-5D measures of pain, activity, mood, and anxiety. 7 Of these, only three utilized mapping studies to predict health state utility values, and only Chan et al developed an original mapping algorithm. 23 They estimated a relationship through OLS regression and forward selection.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] A recent qualitative synthesis review paper by Meregaglia et al identified 28 articles concerned with cost-effective analysis of head and neck cancer treatment options. 7 Of these, only three utilized mapping studies to predict health state utility values, and only Chan et al developed an original mapping algorithm. 23 Meregaglia et al emphasize that additional research on mapping algorithms to convert disease-specific HRQoL results onto preference-based health state utility values would be of value in the population with HNC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations